Hints on the Multiscale Nature of Geomagnetic Field Fluctuations During Quiet and Disturbed Periods. Issue 5 (17th May 2021) - Santarelli, L.; De Michelis, P.; Consolini, G.
Abstract: We analyze the geomagnetic data recorded at 78 stations from 13 to 31 March 2015. Using the empirical mode decomposition (EMD) method, we focus our attention on geomagnetic signal due to sources which are external to the Earth, that is, due to current systems flowing in the ionosphere and magnetosphere. We analyze the short timescale fluctuations ( τ < 200 min) of this magnetic signal, their dependence on magnetic latitude, magnetic local time, and geomagnetic activity. At high geomagnetic latitudes (>|60°|), these short timescale fluctuations constitute more than 30% of the external magnetic field. Their maximum contribution occurs along the auroral oval suggesting that they are mainly triggered by the ionospheric electric current systems active in these regions. A discussion of the relevance of these short timescale magnetic fluctuations to result in a more significant modeling and prediction of geomagnetically induced currents in the auroral zones is also provided. Key Points: The multiscale nature of geomagnetic field fluctuations recorded on the ground is analyzed Short‐timescale magnetic fluctuations constitute a significant contribution to the magnetic field of external origin at high latitudes The main source of short timescale magnetic fluctuations seems to be the occurrence of magnetospheric substorms